2014
DOI: 10.1007/jhep04(2014)056
|View full text |Cite
|
Sign up to set email alerts
|

Lifshitz spacetimes, solitons, and generalized BTZ black holes in quantum gravity at a Lifshitz point

Abstract: Abstract:In this paper, we study static vacuum solutions of quantum gravity at a fixed Lifshitz point in (2+1) dimensions, and present all the diagonal solutions in closed forms in the infrared limit. The exact solutions represent spacetimes with very rich structures: they can represent generalized BTZ black holes, Lifshitz space-times or Lifshitz solitons, in which the spacetimes are free of any kind of space-time singularities, depending on the choices of the free parameters of the solutions. We also find se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 91 publications
(190 reference statements)
2
26
0
Order By: Relevance
“…Recently, we studied the HL gravity in (2+1) dimensions in detail [8], and found further evidence to support the above speculations. In particular, we found all the static (diagonal) solutions of the HL gravity in (2+1) dimensions, and showed that they give rise to very arXiv:1404.3413v4 [hep-th] 4 Feb 2015 rich space-time structures: the corresponding spacetimes can represent the generalized Banados, Teitelboim and Zanelli (BTZ) black holes [9], the Lifshitz space-times, or Lifshitz solitons [10], in which the spacetimes are free of any kind of space-time singularities, depending on the choices of the free parameters of the solutions.…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…Recently, we studied the HL gravity in (2+1) dimensions in detail [8], and found further evidence to support the above speculations. In particular, we found all the static (diagonal) solutions of the HL gravity in (2+1) dimensions, and showed that they give rise to very arXiv:1404.3413v4 [hep-th] 4 Feb 2015 rich space-time structures: the corresponding spacetimes can represent the generalized Banados, Teitelboim and Zanelli (BTZ) black holes [9], the Lifshitz space-times, or Lifshitz solitons [10], in which the spacetimes are free of any kind of space-time singularities, depending on the choices of the free parameters of the solutions.…”
Section: Introductionsupporting
confidence: 55%
“…(2.20) and (2.21). Note that in (2+1)-dimensions the range of z takes its values from the range z ∈ (−∞, ∞), as shown explicitly in [8]. A up bound of z in high-dimensional spacetimes was also found in some numerical solutions in [1,10,12].…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Indeed, recently it was showed that the Lifshitz spacetime (1.4) is a vacuum solution of the HL gravity in (2+1) dimensions, and that the full structure of the z = 2 anisotropic Weyl anomaly can be reproduced in dual field theories [12], while its minimal relativistic gravity counterpart yields only one of two independent central charges in the anomaly. This speculation has been further confirmed by the existence of other types of the Lifshitz spacetimes, including Lifshitz solitons [13,14].…”
mentioning
confidence: 81%